Circadian Clock Regulates Bone Resorption in Mice. (4th March 2016) - Xu, Cheng; Ochi, Hiroki; Fukuda, Toru; Sato, Shingo; Sunamura, Satoko; Takarada, Takeshi; Hinoi, Eiichi; Okawa, Atsushi; Takeda, Shu
ABSTRACT: The circadian clock controls many behavioral and physiological processes beyond daily rhythms. Circadian dysfunction increases the risk of cancer, obesity, and cardiovascular and metabolic diseases. Although clinical studies have shown that bone resorption is controlled by circadian rhythm, as indicated by diurnal variations in bone resorption, the molecular mechanism of circadian clock–dependent bone resorption remains unknown. To clarify the role of circadian rhythm in bone resorption, aryl hydrocarbon receptor nuclear translocator‐like ( Bmal1 ), a prototype circadian gene, was knocked out specifically in osteoclasts. Osteoclast‐specific Bmal1 ‐knockout mice showed a high bone mass phenotype due to reduced osteoclast differentiation. A cell‐based assay revealed that BMAL1 upregulated nuclear factor of activated T cells, cytoplasmic, calcineurin‐dependent 1 ( Nfatc1 ) transcription through its binding to an E‐box element located on the Nfatc1 promoter in cooperation with circadian locomotor output cycles kaput (CLOCK), a heterodimer partner of BMAL1. Moreover, steroid receptor coactivator (SRC) family members were shown to interact with and upregulate BMAL1:CLOCK transcriptional activity. Collectively, these data suggest that bone resorption is controlled by osteoclastic BMAL1 through interactions with the SRC family and binding to the Nfatc1 promoter. © 2016 American Society for Bone and Mineral Research.